Desmodium mottle virus, the first legumovirus (genus Begomovirus) from East Africa - Mollel, Happyness G.; Sseruwagi, Peter; Ndunguru, Joseph; Alicai, Titus; Colvin, John; Navas-Castillo, Jesu´ s; Fiallo-Olive, Elvira (Archives of virology, 2017)
A novel bipartite legumovirus (genus Begomovirus, family Geminiviridae), that naturally infects the wild leguminous plant Desmodium sp. in Uganda, was molecularly characterized and named Desmodium mottle virus. The highest nucleotide identities for DNA-A, obtained from two field-collected samples, were 79.9% and 80.1% with the legumovirus, soybean mild mottle virus. DNA-B had the highest nucleotide identities (65.4% and 66.4%) with a typical non-legumovirus Old World begomovirus, African cassava mosaic virus. This is the first report of a legumovirus in East Africa and extends the known diversity of begomoviruses found infecting wild plants in this continent.
Keywords: Desmodium mottle virus; Legumovirus (genus Begomovirus); East Africa